Degree of convergence of the efficiency of the Polish equity investment funds obtained with measures based on the Sharpe ratio - Sylwester Kozak (e-Finanse: Financial Internet Quarterly, 2017)
Long-term persistence of low interest rates and a decline in attractiveness of investing in low-interest bank deposits generate additional demand for investments in investment funds. In such a situation, it is expected to have widespread use of the investment efficiency measures which take into account not only return, but risk level. The study examines eight measures of efficiency based on the Sharpe ratio. The study uses monthly data for 22 active equity funds over the period 2005- 2015. It was found that the majority of funds were more efficient than the market in periods of moderate economic growth and less effective in the period of strong growth on the capital market. The most efficient funds retain high efficiency in all phases of the economic cycle. The efficiency values obtained using indicators: Shape, Treynor, Jensen, Sortino, Omega, Sharpe-Israelsen and IR were strongly correlated, while values of the UPR indicator were significantly different from the other results.
Keywords: G11; G14; G23; 330; investment decisions; investment efficiency; investment funds; Poland